Does um, the medium, uh, matter? Measuring Fluency through filled pauses in Face-to-Face and Teletandem communicative groups - ZAMORA, Celia Chomón; FINNEGAN, Abbie (The ESPecialist, 2022)
The frequency of hesitational phenomena, such as Filled Pauses (FP) are inversely correlated to the perceived fluency of L2 learners (e.g., DERWING; ROSSITER; MUNRO; THOMSON, 2004; LENNON, 1990; ULLAKONOJA, 2008). The current study investigated the production of these FPs by 66 naive Spanish L2 learners with an L1 of English in two types of oral tasks and compared their frequency in regard to task type and whether they participated in Face-to-Face or Telecollaboration (Teletandem) communicative dyads. Results indicate that while the medium of the tasks did not impact fluency, the task type did.